2017
DOI: 10.1186/s12891-017-1615-0
|View full text |Cite
|
Sign up to set email alerts
|

More preoperative flexibility implies adequate neural pliability for curve correction without prophylactic untethering in scoliosis patients with asymptomatic tethered spinal cord, a retrospective study

Abstract: BackgroundTethered spinal cord is frequently associated with scoliosis. It is still controversial whether a prophylactic untethering is necessary before correction procedure in scoliosis patients with tethered spinal cord. In this study we determined the clinical outcome of a one-stage posterior scoliosis correction without a prophylactic untethering for treating scoliosis with an asymptomatic tethered spinal cord.MethodsSeventeen (5 males and 12 females) scoliosis patients with tethered spinal cords were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Additionally, spinal column shortening has also been found to improve blood flow to the cord which may also contribute towards neurological improvement [46]. Other researchers have reported promising results in CS and diastomatomyelia patients with stable pre-operative neurological deficits undergoing deformity correction without spur resection [26,30,31]. Feng et al concluded safe performance of deformity correction surgery on patients with intact or stable neurological status pre-operatively due to the presence of sufficient space around the split cord to accommodate bony spur during deformity correction [19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, spinal column shortening has also been found to improve blood flow to the cord which may also contribute towards neurological improvement [46]. Other researchers have reported promising results in CS and diastomatomyelia patients with stable pre-operative neurological deficits undergoing deformity correction without spur resection [26,30,31]. Feng et al concluded safe performance of deformity correction surgery on patients with intact or stable neurological status pre-operatively due to the presence of sufficient space around the split cord to accommodate bony spur during deformity correction [19].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive syringomyelia is a good indication that a tethered cord release is indicated. However, cord untethering may be unnecessary in individuals without clinical signs and symptoms of a tethered cord even though tethering is radiographically demonstrable [43][44][45] .…”
Section: Neurosurgerymentioning
confidence: 99%